MANAJEMEN LAKTASI PADA IBU HAMIL DAN MENYUSUI DI MASA PANDEMI COVID-19 DI TANJUNG RIAU KOTA BATAM - Aminah Aatinaa Adhyatma; Dinda Aprilia Putri; Siti Nurlela (Awal Bros Journal of Community Development, 2021)
The success of mothers in breastfeeding their babies can be seen from exclusive breastfeeding. Service activities to increase the capacity of breastfeeding mothers through health counseling regarding lactation management or exclusive breastfeeding during the Covid-19 pandemic because breast milk is very important for endurance in babies and providing adequate amounts of nutrition for the baby's needs. Partners in this kegiatan are pregnant women, nursing mothers, health cadres and obstetrics students. Kegiatan was carried out by the method of lectures and discussions during online counseling through zoom meetings to 41 participants. This counseling uses measuring instruments by taking data online through a google form in the form of pre-tests and post-tests that have been distributed to participants. The results of this counseling have an increase in knowledge with the hope that the increase in knowledge can change the mother's disposition when giving exclusive breastfeeding and have a significant impact on the success of exclusive breastfeeding and always prioritize health rules for mothers and babies when Covid-19 hits. In the conditions of the Covid-19 pandemic, by making efforts in handling, preventing and limiting the transmission of infections, one of which is by encouraging mothers to continue to provide breast milk during the Covid-19 pandemic. It can be concluded that the participants were enthusiastic by giving questions and did not die from zoom meetings for community service counseling.